Terrorism in Space: A Possibility - Ashna Mehmood; Shiza Ahmed (CISS Insight Journal, 2021)
Rapid development in the space tech industry and the proliferation of non-state actors present a wide array of opportunities and challenges, the most significant challenge being the possibility of space terrorism. Although no act of space related terrorism has been recorded yet it is a possibility which cannot be ignored. It requires attention of policymakers at both state and international levels. Lack of discourse analysis and absence of a definitional aspect on the subject makes the threat cataclysmic. This highlights various challenges in space security studies and presents a view point of various motives and capabilities of terrorist organizations in space. It discusses potential targets of space attacks and dilates on the importance of collaborative efforts in tackling the threat, including international organizations` role. Lastly, the paper explores some strategies that may assist policymakers in devising tenable counter-terrorism policy for space.